The MCPH7 Gene Product STIL Is Essential for Dendritic Spine Formation - Tohru Matsuki; Hidenori Tabata; Masashi Ueda; Hideaki Ito; Koh-ichi Nagata; Yumi Tsuneura; Shima Eda; Kenji Kasai; Atsuo Nakayama (Cells)
Dendritic spine formation/maintenance is highly dependent on actin cytoskeletal dynamics, which is regulated by small GTPases Rac1 and Cdc42 through their downstream p21-activated kinase/LIM-kinase-I/cofilin pathway. ARHGEF7, also known as ß-PIX, is a guanine nucleotide exchange factor for Rac1 and Cdc42, thereby activating Rac1/Cdc42 and the downstream pathway, leading to the upregulation of spine formation/maintenance. We found that STIL, one of the primary microcephaly gene products, is associated with ARHGEF7 in dendritic spines and that knockdown of Stil resulted in a significant reduction in dendritic spines in neurons both in vitro and in vivo. Rescue experiments indicated that the STIL requirement for spine formation/maintenance depended on its coiled coil domain that mediates the association with ARHGEF7. The overexpression of Rac1/Cdc42 compensated for the spine reduction caused by STIL knockdown. FRET experiments showed that Rac activation is impaired in STIL knockdown neurons. Chemical long-term potentiation, which triggers Rac activation, promoted STIL accumulation in the spine and its association with ARHGEF7. The dynamics of these proteins further supported their coordinated involvement in spine formation/maintenance. Based on these findings, we concluded that the centrosomal protein STIL is a novel regulatory factor essential for spine formation/maintenance by activating Rac and its downstream pathway, possibly through the association with ARHGEF7.